Identification of partial resistant genotypes of Indian mustard against Alternaria brassicicola under late sown condition in Bihar (Journal of Oilseed Brassica, 2026)
The present investigation was undertaken to identify the partial resistant sources to Alternaria blight (Alternaria brassicicola) in Indian mustard under late sown environmental conditions. Fifteen genotypes of Indian mustard were evaluated in split plot design under artificial inoculation at four different dates of sowing during Rabi season, 2019-20 (12th Nov, 19th Nov, 26th Nov and 3rd Dec). The data obtained from study show the significant effect of date of sowing on percent disease index and area under disease progress curve (AUDPC) under late sown condition due to early onset of diseases at early growth stages coupled with warmer environmental condition. Among different genotypes of Indian mustard, BRRM-101, BRRM-102, BRRM-103, BRRM-104, BRRM-106 line shows less percent disease index as well as area under the disease progress curve.